Global control in Salmonella typhimurium: two-dimensional electrophoretic analysis of starvation-, anaerobiosis-, and heat shock-inducible proteins. - Spector, M P (1986)
The response of Salmonella typhimurium to various forms of environmental stress was examined by using O'Farrell two-dimensional gel electrophoresis. Polypeptides (a total of 110) which quantitatively increased during various starvations, anaerobiosis, or heat shock were identified and cataloged in reference to a standard polypeptide map. Although significant overlap was noted during comparison of proteins induced by different starvations, only a few proteins produced during heat shock or anaerobiosis were also identified as starvation inducible.